Thermal-hydraulic analysis and irreversibility of the MWCNTs-SiO2/EG-H2O non-Newtonian hybrid nanofluids inside a zigzag micro-channels heat sink. (March 2021) - Alnaqi, Abdulwahab A.; Alsarraf, Jalal; Al-Rashed, Abdullah A.A.A.; Afrand, Masoud
Abstract: This study aims to investigate a micro-heat sink (MHS) with zigzag micro-channels subjected to constant heat flux. The MWCNTs – SiO2 /EG – H2 O hybrid nanofluids (HNFs) is used to cool the MHS. The HNFs properties of experimental models are used for this study for the conduction heat transfer coefficient and the rheological behavior of the HNFs as a power-law non-Newtonian (PL-nN) model. The present study also investigates the effective parameters on the thermal hydraulic and irreversibility. The effect of HNF velocity (1–2 m/s), the volume concentration of HNF (0–0.5%) and the zigzag height (0 to 10 mm) on the performance metrics are investigated. In addition, the obtained results and various parameters including heat transfer improvement, pressure drop (∆ P ), and maximum temperature ( T Max ) of the MHS are investigated in each section. Eventually, the results revealed that increasing the velocity increases the heat dissipation from the MHS. On the other hand, increasing the zigzag length of the channel increases heat transfer from the MHS's surface, and thus, improves heat transfer, which is associated with an increase in the ∆ P of the passing fluid. The increase in the concentration of nanoparticles and MWCNTs cause to a considerable increase in viscosity, which dramatically increases the pumping power inside the MHS. Increasing the height of zigzags increases the collision of fluid to the walls of the micro-channels and increases the total entropy generation.